(untitled) (Journal of Civil Engineering Researchers, 2023)
In this article using the principles and relationships governing fracture mechanics and finite elements cracking in the first mode for reinforced concrete beams reinforced with FRP sheets are analyzed and modeled. In this method to simulate the crack in reinforced beams, the relations for determining the stress intensity coefficients with the presence of rebars and reinforcement sheets are developed. Here, it is assumed that a composite sheet is completely bound to the bottom surface of the beam under pure bending moment. In the proposed method beam components are divided into two categories, including components without cracks and components with cracks. In components without cracks, relations, equations, and the conventional stiffness matrix governing the beam are used, taking into account the changes in the moment of inertia caused by the presence of reinforcements and FRP sheets. In the finite component with a crack, the crack profile is simulated by creating a geometric defect in the beam section. So that the reduction in the hardness of the component with a crack is equivalent to the change in the dimensions of the discontinuity. Here, the changes in the hardness of the cracked component are calculated and presented as a function of the modified stress intensity coefficients. To ensure the correctness and accuracy of the presented method, all the analyzes are implemented in Abaqus software. The comparison of the obtained results shows that the presented method is a suitable method for the analysis of reinforced concrete structures resistant to cracking. So that it can be extended and developed for other models with proper accuracy.